Histologic pattern of invasion and epithelial-mesenchymal phenotype predict prognosis in squamous carcinoma of the head and neck. (December 2018) - Wolf, Gregory T.; Winter, William; Bellile, Emily; Nguyen, Ariane; Donnelly, C.R.; McHugh, Jonathan B.; Thomas, Dafydd; Amlani, Lahin; Rozek, Laura; Lei, Yu L.; ,
Highlights: E-cadherin expression correlated inversely with increased vimentin expression. Vimentin positive cells correlated with levels of tumor infiltrating lymphocytes. Loss of E-cadherin was associated with low or absent SOX2 expression. SOX2 expression and pattern of invasion predicted favorable overall and relapse free. Pattern of invasion correlated inversely with tumor infiltrating lymphocytes. Low grade invasion predicted improved survival for primary surgery but not chemoradiation. Abstract: Introduction: Disruption of E-cadherin function and increased expression of vimentin and the transcriptional oncogene, SOX2, are thought to characterize epithelial to mesenchymal transition (EMT) in HNSCC that contributes to invasive and metastatic behavior. To determine if such changes relate to prognosis or host immune response, expression of these markers and correlations with clinical characteristics, histologic worst pattern of invasion (WPOI) and tumor infiltrating lymphocytes (TIL) and survival were assessed. Methods: Immunohistologic expression of markers was determined in tissue microarrays from 274 previously untreated HNSCC patients. Expression was correlated with levels of TILs in microcores and WPOI in biopsy specimens. Correlations were assessed by Kruskal-Wallis testing and Spearman correlation coefficients where appropriate. Overall and relapse-free survival were analyzed with Cox proportional hazards models. Median follow up was 60.0 months. Results: Loss of E-cadherin expression was significantly associated with low or absent SOX2 expression (R = 0.433, p < 0.0001). SOX2 expression and low grade WPOI were significantly associated with favorable overall (OS) and relapse free (RFS) survival in multivariable analysis. E-cadherin expression did not correlate with TILs, however WPOI score correlated indirectly with CD4, CD8, and FoxP3 levels. When grouped by primary treatment, lower grades (1, 2) of WPOI predicted improved RFS and OS in patients treated with primary surgery but not for patients treated with chemoradiation. Conclusion: The findings suggest that SOX2 expression and WPOI are significant prognostic factors and that WPOI correlates with decreased T cell infiltration. The combination of markers and TILs might be useful in selecting patients for primary surgery.